Pemaparan Sense Of Design Dalam Desain Komunikasi Visual Pada Goa Soekarno Di Kabupaten Sumenep - Ahmad Rosikur Rahman; Hidayat; Anis Kurli (Universitas Budi Luhur, 2026)
This study aims to explore and analyze the application of sense of design in visual communication design at the Goa Soekarno tourist destination in Sumenep Regency. Despite its rich historical and cultural value, the site lacks optimal and engaging visual communication elements. This research employs a descriptive qualitative method through field observation, visual documentation, and interviews with site managers and visitors. The findings reveal that design elements such as typography, color, layout, and illustration are not yet fully utilized to reflect the site's identity or enhance its appeal. The study recommends the implementation of sense of design principles—emphasizing aesthetics, function, and symbolic meaning—to create more effective visual communication media that can strengthen the destination's image. This research contributes to the development of context-based and locally rooted tourism promotion strategies through visual design.